Tissue-resident memory T cells: decoding intra-organ diversity with a gut perspective - Mari Murakami (BMC, 2024)
Abstract Tissue-resident memory T cells (TRM) serve as the frontline of host defense, playing a critical role in protection against invading pathogens. This emphasizes their role in providing rapid on-site immune responses across various organs. The physiological significance of TRM is not just confined to infection control; accumulating evidence has revealed that TRM also determine the pathology of diseases such as autoimmune disorders, inflammatory bowel disease, and cancer. Intensive studies on the origin, mechanisms of formation and maintenance, and physiological significance of TRM have elucidated the transcriptional and functional diversity of these cells, which are often affected by local cues associated with their presence. These were further confirmed by the recent remarkable advancements of next-generation sequencing and single-cell technologies, which allow the transcriptional and phenotypic characterization of each TRM subset induced in different microenvironments. This review first overviews the current knowledge of the cell fate, molecular features, transcriptional and metabolic regulation, and biological importance of TRM in health and disease. Finally, this article presents a variety of recent studies on disease-associated TRM, particularly focusing and elaborating on the TRM in the gut, which constitute the largest and most intricate immune network in the body, and their pathological relevance to gut inflammation in humans.